Enhanced photoluminescence and solar cell performance via Lewis base passivation of organic-inorganic lead halide perovskites - Noel, N; Abate, A; Stranks, S; Parrott, E; Burlakov, V; Goriely, A; Snaith, H (American Chemical Society, 2014)
Organic-inorganic metal halide perovskites have recently emerged as a top contender to be used as an absorber material in highly efficient, low-cost photovoltaic devices. Solution-processed semiconductors tend to have a high density of defect states and exhibit a large degree of electronic disorder. Perovskites appear to go against this trend, and despite relatively little knowledge of the impact of electronic defects, certified solar-to-electrical power conversion efficiencies of up to 17.9% have been achieved. Here, through treatment of the crystal surfaces with the Lewis bases thiophene and pyridine, we demonstrate significantly reduced nonradiative electron-hole recombination within the CH(3)NH(3)PbI(3-x)Cl(x) perovskite, achieving photoluminescence lifetimes which are enhanced by nearly an order of magnitude, up to 2 μs. We propose that this is due to the electronic passivation of under-coordinated Pb atoms within the crystal. Through this method of Lewis base passivation, we achieve power conversion efficiencies for solution-processed planar heterojunction solar cells enhanced from 13% for the untreated solar cells to 15.3% and 16.5% for the thiophene and pyridine-treated solar cells, respectively.